Addressing the gaps in environmental protections within the protocol on investment to the African Continental Free Trade Area - Ngobeni, Tinyiko (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2025.